Empowering Vocational Students' Entrepreneurial Readiness Through Field Practice Experience, Self-Reliance, and Interest in Entrepreneurship - Hilmi, Mohamad Alfin; Ekohariadi, Ekohariadi; Rijanti, Tri; Suhartini, Ratna (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to analyze the influence of Field Work Practice (PKL), self-reliance, and entrepreneurial interest on students’ entrepreneurial readiness, with perceived competence in productive subjects as a mediating variable. The research focuses on students of the Light Vehicle Engineering (TKR) major at vocational high schools in the Kediri region of East Java, Indonesia. Method: The study employed a quantitative approach using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique. Data were collected via a structured, validated questionnaire distributed to 388 respondents and analyzed using SmartPLS 3.0 software. Results: The findings indicate that PKL experience, self-reliance, and entrepreneurial interest significantly influence students’ entrepreneurial readiness. Moreover, perceived competence mediates the relationship between the exogenous variables and entrepreneurial readiness. The integrated model demonstrated good reliability, validity, and explanatory power. Novelty: This study offers a comprehensive model by integrating experiential, psychological, and academic constructs to predict entrepreneurial readiness in vocational students. Unlike previous studies that treated these variables independently, this research highlights the mediating role of perceived competence, providing new insight for vocational education development and curriculum design.